Lifestyle of type 2 diabetes mellitus patients with peripheral neuropathy: Phenomenological study - Sukhri Henanto Ritonga; Eva Decroli; Brian Sri Prahastuti; Elly Usman; Mudjiran; Adang Bachtiar; Afnwardi; Husna Yetti (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the lifestyle-related characteristics of people having type 2 diabetes mellitus with peripheral neuropathy. Method: The phenomenological study was conducted from July 5 to September 18, 2021, at Sadabuan Health Centre, Batunadua Health Centre and Wek 3 Health Centre, Padangsidimpuan, Indonesia, and comprised diabetic neuropathy patients who had cognitive impairment, anxiety and depression. Data was collected using in-depth interviews. Data was analysed using Collaizi’s method. Results:There were 8 subjects with mean age 48.38±13,606 years (range: 27-65 years), and mean duration of diabetes was 6±3.207 years. The majority of participants in this study were women 6 (75%). There were 7 themes that emerged from the collected data: level of physical activity, diet, sleep pattern, habit of consuming sweet drinks, smoking habit, social interaction, and self-care. Conclusion: Diabetes mellitus patient with peripheral neuropathy had not been able to completely switch to a healthier lifestyle. Keywords: Neuropathies, Diabetes, Depression, Dysfunction, Smoking, Anxiety, Habits, Sleep, Diet, Social Interaction, Exercise, Life Style.